Thyroid storm during the recovery phase after non-thyroid surgery in a hyperthyroid patient: a case report and literature review - Zeng, Jiyu; Yang, Ting; Wu, Li (Frontiers in Surgery, 2025)
BackgroundThyroid storm is a life-threatening endocrine emergency characterized by an acute exacerbation of thyrotoxicosis, often triggered by stressors such as surgery or infection, with a mortality rate of 8%–25%. Although the risk is well-documented in thyroid surgeries, perioperative thyroid storm following non-thyroid procedures is exceedingly rare, posing diagnostic and therapeutic challenges. This case report and literature review aim to highlight the clinical features and management strategies for perioperative thyroid storm in non-thyroid surgical patients through a case analysis and literature review.Case presentationA 53-year-old Chinese male with a 20-year history of poorly controlled hyperthyroidism (irregular medication adherence) underwent closed reduction and intramedullary nailing for a right femoral fracture. Preoperative evaluation revealed mildly elevated free triiodothyronine (FT3: 6.87 pmol/L) and profoundly suppressed thyroid-stimulating hormone (TSH: <0.01 mIU/L). Antithyroid medication was omitted on the day of surgery. Following surgery and transfer to the recovery room, the patient demonstrated delayed emergence from anesthesia, with a Burch-Wartofsky score of 45 and persistent tachycardia (heart rate 144 bpm), meeting Grade 1 thyroid storm criteria per Japan Thyroid Association guidelines, indicating a definitive thyroid storm. After about one hour, the patient was diagnosed with thyroid crisis. Intravenous hydrocortisone (100 mg) and continuous esmolol infusion were promptly initiated, leading to gradual heart rate stabilization at 120 bpm. Approximately 20 minutes later, the patient regained full consciousness and met criteria for discharge from the recovery room. The patient was discharged on postoperative day 10 without complications.ConclusionsThis case underscores that non-thyroid surgery can precipitate thyroid storm in hyperthyroid patients, even with atypical presentations (e.g., absence of hyperpyrexia). Early recognition relies on vigilance toward tachycardia and altered mental status. Perioperative management should emphasize: (1) rigorous preoperative optimization of thyroid function to achieve euthyroidism; (2) vigilant postoperative monitoring for early signs of thyroid storm; and 3) prompt diagnosis using the Burch-Wartofsky scale and guideline-based criteria, followed by combined therapy with beta-blockers, corticosteroids, and antithyroid drugs. This case uniquely demonstrates that non-thyroid surgery can precipitate thyroid storm without classic hyperthermia, highlighting the need for standardized monitoring protocols in hyperthyroid surgical patients.